Strategic information management: model based on literature review (Advances in Knowledge Representation, 2023)
This is a work that presents the results of qualitative research that aimed to propose a model of strategic information management to be used by organizations. The article reports the results of a literature review regarding models and criteria for the strategic information management, having as an unfolding the proposition of its own model. A bibliographic research was carried out to analyze the scientific production on criteria and models used for strategic information management and, after researching articles and other publications, the results indicated the existence of 50 models and 40 most frequently cited criteria. This survey served as the basis for proposing a strategic information management model composed of 8 stages, namely: 1) Identification of needs; 2) Collection; 3) Treatment and analysis; 4) Organization; 5) Storage; 6) Distribution; 7) Use and; 8) Assessment. The model proposed in this study is not defined as something definitive, untouchable. It is a guide, an orientation for those who seek to manage information strategically. The main lesson to be learned is that organizations, regardless of the sector or regime to which they are inserted, can no longer ignore the importance of the process of managing their information.